Vocal self-perception of trans women and trans men (Research, Society and Development, 2022)
Purpose: To characterize vocal self-perception in trans men and women. Methods: This is an observational, transversal and descriptive research. It was approved by the Research Ethics Committee of the Federal University of Sergipe with protocol number 4.333.500 and the Certificate of Presentation of Ethical Appreciation (CAAE) 3443772.1.0000.5546. Sixty-nine transgender people who used an outpatient clinic focused on the transsexualizing process participated in the research. Data from the anamnesis and from the Voice Quality of Life (QVV) instruments and the Transgender Woman Voice Questionnaire (TWVQ) were used. Descriptive and inferential analysis was performed. Results: There was a positive correlation between the socio-emotional domain of the QVV with the voice note, and a negative correlation of the TWVQ with the variables voice perception, perception of others' impression of their voice and current voice. Trans men and women differed on the perception of the ideal voice. Conclusion: It was found a dissatisfaction with the perception of trans people about their voices and a low quality of life in voice, with no difference between trans women and men. Furthermore, trans women demonstrated a vocal impact in their daily life, mainly influenced by the perception of the other, in the search for social acceptance and minimization of the risks that gender prejudice imposes.